Into thin air: prehistoric intensive crop management in high altitude western Tibet - Ritchey, Melissa M.; Tang, Li; Vaiglova, Petra; Lu, Hongliang; Sun, Yufeng; Frachetti, Michael D.; Liu, Xinyi (Frontiers in Environmental Archaeology, 2024)
High-altitude conditions on the Tibetan Plateau are often depicted as an inhospitable environment for conventional farming, yet evidence shows that communities in western Tibet grew ecologically hardy crops such as 6-row barley (Hordeum vulgare) by at least the 1 st millennium BCE, at locations about 4000 meters above sea level (masl). However, little is known about the specific cultivation strategies and culinary traditions that these agropastoral communities developed. Stable carbon and nitrogen isotope compositions of grains inform growing conditions and provide much needed insight into the cultivation strategies in such a unique environment. We use δ 13 C and δ 15 N values of archaeologically recovered barley remains to investigate past watering and soil-management strategies. Our results infer high labor investment in manuring and watering in barley farming. This suggests an intensive cultivation system in Western Tibet, 1000 BCE -1000 CE, despite the high-altitude pastoral landscape.